KONSTRUKSI PARENTING ISLAMI DARI PERSPEKTIF HADIS DALAM MERESPONS ISU CHILD GROOMING DI ERA DIGITAL - Dhofirul Yahya (Universitas Muhammadiyah Bandung, 2026)
Child grooming in the digital age is a form of manipulation of children through social media, messaging apps, and other online platforms that has the potential to lead to sexual exploitation. This phenomenon demonstrates that children need not only legal protection but also strengthened family parenting that can build moral, emotional, and digital resilience. This study aims to analyze the construction of Islamic parenting from the perspective of hadith as a preventive response to child grooming in the digital age. This is a qualitative, literature-based study using a thematic-hadith approach. Primary data sources consist of hadiths regarding parental responsibility, child protection, moral education, and faith development, while secondary data consists of literature on child grooming, Islamic parenting, and child protection in the digital space. The data were analyzed through reduction, thematic categorization, and contextual interpretation of relevant hadiths. The results indicate that the Islamic parenting framework in response to child grooming encompasses five main pillars: strengthening children’s monotheism and moral character; parental supervision and responsibility (ri‘ayah); open communication within the family; fostering proper social etiquette and physical protection; and digital literacy grounded in Islamic values. These five pillars position parents not only as caregivers, but also as protectors, educators, and guides in their children’s use of digital spaces. Thus, hadith-based Islamic parenting can serve as a preventive framework for building children’s resilience against the threat of child grooming in the digital age.